2021
DOI: 10.3389/fmicb.2021.751006
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Molecular Characterization of Abundant tet(X) Variants Among Diverse Bacterial Species of Chicken Origin in Jiangsu, China

Abstract: Many novel tigecycline-inactivating enzymes encoded by tet(X) variants from different bacteria were discovered since the plasmid-mediated tet(X3) and tet(X4) genes conferring high-level resistance to tigecycline in Enterobacterales and Acinetobacter were reported. However, there have been no comprehensive studies of the prevalence of different tet(X) variants in poultry farms. In this study, we collected 45 chicken fecal samples, isolated tet(X)-positive strains, and performed antimicrobial susceptibility test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…An analysis for the genetic environments of bla OXA−58 showed that a truncated IS Aba3 element was located upstream of bla OXA−58 and a complete IS Aba3 element downstream of it. The genetic context found in the present study was consistent with that in plasmid pLHC22-2-tetX-162k (CP084298) in a previous study ( 19 ). In addition, the presence of two intact IS Aba3 copies in opposite orientation up-stream and down-stream of bla OXA−58 was described in a series of studies and led to the assumption that IS Aba3 might play a role in the transfer of bla OXA−58 ( 22 , 34 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…An analysis for the genetic environments of bla OXA−58 showed that a truncated IS Aba3 element was located upstream of bla OXA−58 and a complete IS Aba3 element downstream of it. The genetic context found in the present study was consistent with that in plasmid pLHC22-2-tetX-162k (CP084298) in a previous study ( 19 ). In addition, the presence of two intact IS Aba3 copies in opposite orientation up-stream and down-stream of bla OXA−58 was described in a series of studies and led to the assumption that IS Aba3 might play a role in the transfer of bla OXA−58 ( 22 , 34 ).…”
Section: Discussionsupporting
confidence: 92%
“…GenBank database searches identified the complete sequences of seven plasmids from Acinetobacter spp. with p19110F47-2 query coverage ranges from 40 to 87% ( Supplementary Figure 2 ), and most of these plasmids harbored both bla OXA−58 and tet (X) orthologs ( 19 , 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ecological niches in which plasmid-encoded TIG resistance tet (X) genes have been detected are shown in Table 1 . Clearly, there is increasing evidence of plasmid-encoded TIG resistance tet (X) genes reported in countries across Europe, Asia, United States, South America, and Africa involving humans, food animals, including chickens, pigs, ducks, pigeons, geese, and cattle, as well as companion animals, food animal products (meats), aquaculture and environment such as soil, livestock-farm water, wastewaters, sewages, and wildlife as reservoirs of MTR ( Bai et al, 2019 ; Chen et al, 2019a , b , 2020 , 2021 ; He et al, 2019 ; Sun C. et al, 2019 , 2020 ; Sun J. et al, 2019 ; Cao et al, 2020 ; Cui et al, 2020 , 2021b ; Ding et al, 2020 ; Du et al, 2020 ; He T. et al, 2020 ; Li et al, 2020 , 2021f ; Ma et al, 2020 ; Pan et al, 2020 ; Ruan et al, 2020 ; Song et al, 2020 ; Wang et al, 2020a , b ; Zhang et al, 2020b , 2021 ; Zheng et al, 2020 ; Cheng et al, 2021a , b ; Feng et al, 2021 ; Hirabayashi et al, 2021a , b ; Hsieh et al, 2021 ; Li et al, 2021e , f ; Lu et al, 2021 ; Marathe et al, 2021 ; Martelli et al, 2021 ; Mohsin et al, 2021 ; Soliman et al, 2021 ; Sun et al, 2021a , b ; Tang et al, 2021 ; Wang et al, 2021f , g ; Xu et al, 2021 ; Yu Y. et al, 2021 ; Wu et al, 2022 ; Zhai et al, 2022 ). We further demonstrate this, through the specific reservoirs in which plasmid-borne transmissible tet (X) and tmexCD-toprJ genes have been detected as shown in Table 2 .…”
Section: Distribution Reservoirs and Traits Of Mobile Tigecycline Res...mentioning
confidence: 99%
“…However, some chromosomal mobile elements like ICEs and transposons, also contribute to the transfer of tet (X). For example, the mobility of chromosome-borne tet (X15) was associated with IS Aba1 -bound composite transposon Tn 6866 ( Li et al, 2021b , e , f ), tet (X4) was flanked by IS 91 family transposase genes in chromosome of Shewanella xiamensis ( Dao et al, 2022 ), and the location of transferable tet (X6) in ICE have also been reported ( He D. et al, 2020 ; Wang et al, 2021c ; Li et al, 2022 ). ICE are modular MGEs integrated into a host genome and are passively propagated during chromosomal replication and cell division.…”
Section: Distribution Reservoirs and Traits Of Mobile Tigecycline Res...mentioning
confidence: 99%
“…A previous study only collected three E. coli strains from poultry chicken meat, wild bird, and the slaughterhouse wastewater in Pakistan, and these strains were found in a variety of phylogenetic clades [ 6 ]. Similarly, another study identified four tet (X4)-positive E. coli (8.9%) isolates in 45 chicken fecal samples [ 7 ]. Recently, a systematic retrospective study collected 613 tet (X4)-positive E. coli isolates from public databases, and found that pigs and their products were the most common vehicles (n = 162) for tet (X4) dissemination, followed by human (n = 122), chickens (n = 60), and the environment (n = 49) [ 8 ], suggesting a substantial difference in the prevalence of tet (X4) between chicken E. coli and pig E. coli [ 2 ].…”
Section: Introductionmentioning
confidence: 99%